Impact Of Corporate Governance Mechanism On Capital Structure Decision On Non-Financial Sectors Of Emerging Countries - Rahman, Dr. Shams Ur; Adnan, Muhammad; Jan, Nasim Akhtar; Nasreen, Dr. Farah; Shah, Dr Naveed Hussain; Iqbal, Arshad (Migration Letters, 2024)
The study aimed to evaluate the effect of Corporate Governance Dynamic on Leverage on non-financial sectors of emerging countries (Pakistan, India, and Bangladesh ) during the study period of 2014 to 2023. The nature of the study is quantitative and secondary therefore data has been extracted from the respective websites of the companies and stock exchange from the pharmaceutical, cement, and food industries. Moreover, the Random effect model was used to on the bases of diagnostic test to identify the cause and effect. The findings of the study reveal that director remuneration, and board education in Pakistan showed positive and significant effects but Board size, board experience showed significant and negative effects on the capital structure decision. While board diversity, firm size found an insignificant association with leverage in Pakistan. For firm size showed an insignificant effect but board size, direct remuneration, and board education showed a negative and significant effect on leverage while board experience, board diversity was a positive and significant effect on leverage. Moreover, in India, board experience, board diversity, and board education was a significant but negative effect on leverage but board size, direct remuneration, firm size showed a positive and significant effect on the leverage of non-financial firms.